Evolving Concepts in Endothelial Pathobiology of Pulmonary Arterial Hypertension. Issue 8 (18th May 2022) - Cober, Nicholas D.; VandenBroek, M. Martin; Ormiston, Mark L.; Stewart, Duncan J.
Abstract : Pulmonary arterial hypertension (PAH) is a deadly disease, characterized by increased vascular resistance, pulmonary arteriolar loss, and occlusive arterial remodeling, leading to eventual right heart failure. Evidence increasingly points to the pulmonary endothelium as a central actor in PAH. Endothelial cell apoptosis can result directly in distal lung arteriolar pruning and indirectly in the formation of complex and occlusive arterial lesions, reflecting an imbalance between endothelial injury and repair in the development and progression of PAH. Many of the mutations implicated in PAH are in genes, which are predominantly, or solely, expressed in endothelial cells, and the endothelium is a major target for therapeutic interventions to restore BMP signaling. We explore how arterial pruning can promote the emergence of occlusive arterial remodeling mediated by ongoing endothelial injury secondary to hemodynamic perturbation and pathological increases in luminal shear stress. The emerging role of endothelial cell senescence is discussed in the transition from reversible to irreversible arterial remodeling in advanced PAH, and we review the sometimes conflicting evidence that female sex hormones can both protect or promote vascular changes in disease. Finally, we explore the contribution of the endothelium to metabolic changes and the altered inflammatory and immune state in the PAH lung, focusing on the role of excessive TGFβ signaling. Given the complexity of the endothelial pathobiology of PAH, we anticipate that emerging technologies that allow the study of molecular events at a single cell level will provide answers to many of the questions raised in this review.